The CARD-carrying caspase Dronc is essential for most, but not all, developmental cell death in Drosophila. - Xu, D.; Li, Y.; Arcaro, M.; Lackey, M.; Bergmann, A. (Development, 2005)
The initiator caspase Dronc is the only Drosophila caspase that contains a caspase activation and recruitment domain (CARD). Although Dronc has been implicated as an important effector of apoptosis, the genetic function of dronc in normal development is unclear because dronc mutants have not been available. In an EMS mutagenesis screen, we isolated four point mutations in dronc that recessively suppress the eye ablation phenotype caused by eye-specific overexpression of hid. Homozygous mutant dronc animals die during pupal stages; however, at a low frequency we obtained homozygous adult escapers. These escapers have additional cells in the eye and wings that are less transparent and slightly curved down. We determined that this is due to lack of apoptosis. Our analyses of dronc mutant embryos suggest that dronc is essential for most apoptotic cell death during Drosophila development, but they also imply the existence of a dronc-independent cell death pathway. We also constructed double mutant flies for dronc and the apoptosis inhibitor diap1. dronc mutants can rescue the ovarian degeneration phenotype caused by diap1 mutations, confirming that dronc acts genetically downstream of diap1.